Large In-mask Motion during Frameless Radiosurgery of a Brain Metastasis - Harat, Maciej; Furtak, Jacek (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Frameless radiosurgery is now a common alternative to traditional in-frame treatment. Several dosimetric studies have reported small in-mask positioning inaccuracies during frameless radiosurgery. We present a case of an uncommonly large deviation in in-mask motion detected offline in a patient undergoing linear accelerator–based frameless radiosurgery. Our case illustrates how the use of a thermoplastic mask can lead to unacceptable setup errors for passive image-guided radiosurgery. The case underlines the need for correct patient preparation, adequate time between mask molding and computed tomography, and routine intrafraction imaging. Image-guided positioning is recommended to achieve clinically acceptable setup accuracy (< 1 mm) for stereotactic radiosurgery.
Keywords: frameless radiosurgery; LINAC; stereotactic radiosurgery